2019
DOI: 10.1016/j.patrec.2019.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the best edit in perturbation-based iterative refinement algorithms to compute the median string

Abstract: Strings are a natural representation of biological data such as DNA, RNA and protein sequences. The problem of finding a string that summarizes a set of sequences has direct application in relative compression algorithms for genome and proteome analysis, where reference sequences need to be chosen. Median strings have been used as representatives of a set of strings in different domains. However, several formulations of those problems are NP-Complete. Alternatively, heuristic approaches that iteratively refine… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(25 citation statements)
references
References 17 publications
0
24
0
Order By: Relevance
“…We conduct experiments to compare the quality of the approximated median for S obtained using pivots in P respect to the reference algorithm [21] which operates over the whole S. We used the average distance to the median (MAD) as a quality measure and the number of edit distance computed while the algorithms are running as a measure of the speed.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We conduct experiments to compare the quality of the approximated median for S obtained using pivots in P respect to the reference algorithm [21] which operates over the whole S. We used the average distance to the median (MAD) as a quality measure and the number of edit distance computed while the algorithms are running as a measure of the speed.…”
Section: Resultsmentioning
confidence: 99%
“…[1] improved the idea of [2] and achieved more 978-1-7281-5613-2/19/$31.00 ©2019 IEEE solid outcomes, increasing the convergence speed compared with [14] and maintaining the quality of the approximated median. One step further, in [21], the heuristic to select the best edit operation considerate the repercussions of each edition in all strings of the set, improving the ranking of editions. Another approach for the Median String Problem is as a Linear Programming problem, this is the case of [23], which give a lower bound and analyze the cases where the true median cannot be achieved, but do not obtain the median string.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…These transformations can be only three possible operations: insertion, deletion, and substitution. Using a similar principle as a basis, the work by Mirabal et al (2019) also considers the different transformations reported by the edit distance and proposes an innovative ranking strategy with which to establish the correct order in which they must be applied. Other research efforts can be found in Kaysar and Khan (2020), in which an approximate version of the median string is computed using Markov chains for DNA motif classification, or in Chakraborty et al (2021), which performs this approximation by resorting to a probabilistic framework based on the so-called Ulam metric.…”
Section: Background In Data Reductionmentioning
confidence: 99%